2021
DOI: 10.1007/s11783-021-1415-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects and risk control of antibiotic resistance genes in the organic solid waste aerobic composting system: A review

Abstract: Antibiotic resistance genes (ARGs) have been diffusely detected in several kinds of organic solid waste, such as livestock manure, sludge, antibiotic fermentation residues, and food waste, thus attracting great attention. Aerobic composting, which is an effective, harmless treatment method for organic solid waste to promote recycling, has been identified to also aid in ARG reduction. However, the effect of composting in removing ARGs from organic solid waste has recently become controversial. Thus, this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…However, in our study, aadA and blaTEM were more prevalent genes. Our results demonstrated that animal manure are important reservoirs of ARGs; thus, it is recommended to develop specific management practices such as aerobic and hyperthermophilic composting for farm amendment of different types of animal manure [ 126 , 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, aadA and blaTEM were more prevalent genes. Our results demonstrated that animal manure are important reservoirs of ARGs; thus, it is recommended to develop specific management practices such as aerobic and hyperthermophilic composting for farm amendment of different types of animal manure [ 126 , 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics genes have been discovered in all kinds of environment even amongst the so-called pristine and controlled environments like compost thus supporting the fact that these genes have their origin in the environment [ 1 , 8 , 29 , 30 ]. Yet, the role of environmental factors in the spread of antimicrobial resistance is largely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…The aerobic composting of agricultural and forestry solid waste is of great importance. Aerobic composting is a mature and low-cost technology and is an effective way to resource, reduce, and render harmless waste crop straw [11][12][13]. Composting is the gradual degradation of unstable organic matter in the compost material through high-temperature aerobic fermentation into a stable, crop-friendly, and soil-improving compost product, which is returned to the farmland to improve soil fertility and achieve agricultural cycle production [14].…”
Section: Introductionmentioning
confidence: 99%